ANALYSIS OF ERROR WRITING ON OFFICIAL LETTER AT THE MUHAMMADIYAH TANGERANG UNIVERSITY 2023 - Sayeti, Ety; Sulaeman, Agus; Goziyah, Goziyah (Jurnal Dinamika UMT, 2023)
Based on the results and discussion that have been explained in this study, it can be seen that official letters written by writers at the University of Muhammadiyah Tangerang still have language errors, in the type of writing letters in the letters they produce. Some of these mistakes can occur due to several factors such as lack of understanding of spelling writing in accordance with Indonesian rules by official letter writers, accustomed to making the same language mistakes or have never carried out training related to official letter writing. Thus, there are still some language errors made by official letter writers at the University of Muhammadiyah Tangerang